Literature Review on Factors Influencing Job Satisfaction: Variables of Work Environment, Workload, and Compensation - Ibrahim, Tony; Yosepha, Sri Yanthy (Dinasti Publisher, 2025)
Employee job satisfaction serves as a critical benchmark in achieving the objectives of an organization. It is regarded as highly significant and crucial, prompting human resource management practitioners, who oversee and manage human resources, to frequently conduct research. Prior studies play an essential role in supporting new research or academic articles. This scientific article aims to reinforce theoretical foundations and elucidate phenomena related to the relationships or influences among the variables under investigation. This article specifically reviews and analyses various factors that impact employee job satisfaction as a component of human resource management. Based on the identification and literature review conducted, it has been found that: 1) the work environment has a significant influence on job satisfaction; 2) workload affects job satisfaction; and 3) compensation impacts job satisfaction. Relevant prior research serves as a foundational reference for the literature review in this academic article, thereby providing a basis for future research that is expected to support organizational strategies and policies, particularly in the management of human resources.